Implementasi Regulasi Daerah Dalam Penyelenggaraan Penanaman Modal: Studi Perda Kota Bandung Nomor 4 Tahun 2022 - Angelica; Claureria Angie Ely; Sheren Michi Tjandra; Udin Silalahi; Joy Zaman Felix Saragih (CV. Ulil Albab Corp, 2026)
Regional regulations play a strategic role in supporting investment activities as part of regional autonomy and local economic development. Their success depends not only on the establishment of legal norms but also on their implementation in government practice. Regional governments are expected to create a favorable investment climate by enforcing regulations that provide legal certainty, business convenience, and protection for investors. Bandung Regional Regulation Number 4 of 2022 concerning the Implementation of Investment Activities is a legal instrument that regulates service mechanisms, facilitation, and control of investment activities in Bandung. This study aims to analyze the implementation of regional regulations in investment administration through an examination of Bandung Regional Regulation Number 4 of 2022. The research method used is normative juridical with statutory and conceptual approaches. The findings show that the regulation has provided an adequate legal framework for investment activities. However, its implementation still requires consistency, coordination among regional agencies, and alignment with national investment policies to achieve its objectives effectively and support sustainable regional investment growth. Therefore, strengthening the implementation of regional regulations is essential to improve investor confidence, increase regional competitiveness, attract more investment, and encourage balanced economic development that benefits both government and society in general.